1990
DOI: 10.1002/sia.740150406
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray photoelectron spectroscopic studies of thin film oxides of cobalt and molybdenum

Abstract: Surface oxidation reactions of cobalt, molybdenum and mixed cobalt-molybdenum metals have been investigated using x-ray pbchelectron spectroscopy (XPS). Tbe oxide stoicbiometries have been determined from XPS intensity measurements Sucb quantification has been important in identifying oxide compositions with cbaracteristic XPS spectra. A number of discrete binary molybdenum oxides have been characterized after reactions at 2OOOC and pressures ranging from 1 atm to Pa. At the lowest pressure, the Mo 3d spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
92
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(107 citation statements)
references
References 13 publications
11
92
0
1
Order By: Relevance
“…According to this analysis, the recorded Co 2p 3/2 peaks were located at 781.2 ± 0.1 eV and were asymmetric to the high binding energy side. This value occurs in between the values reported earlier to correspond to Co 2+ in CoO (780.0 ± 0.2 eV for the 2p 3/2 line) [20,21], and to Co 2+ in Co(OH) 2 (782.0 ± 0.1 eV for the 2p 3/2 line) [22]. Both lines are readily discerned from that corresponding to metallic cobalt, Co 0 (778.0 ± 0.2 eV for the Co2p 3/2 line) [20,23].…”
Section: Resultssupporting
confidence: 83%
“…According to this analysis, the recorded Co 2p 3/2 peaks were located at 781.2 ± 0.1 eV and were asymmetric to the high binding energy side. This value occurs in between the values reported earlier to correspond to Co 2+ in CoO (780.0 ± 0.2 eV for the 2p 3/2 line) [20,21], and to Co 2+ in Co(OH) 2 (782.0 ± 0.1 eV for the 2p 3/2 line) [22]. Both lines are readily discerned from that corresponding to metallic cobalt, Co 0 (778.0 ± 0.2 eV for the Co2p 3/2 line) [20,23].…”
Section: Resultssupporting
confidence: 83%
“…This value, which is identical to the one we reported earlier for Co-loaded nZVI (Üzüm et al, in press), occurs well above that reported in the literature for metallic cobalt, Co 0 , i.e. 778.0 ± 0.2 eV (Wagner et al, 1979;McIntyre and Cook, 1975), and is close to those reported earlier for Co 2+ in cobalt oxide (780.0 ± 0.2 eV) (McIntyre and Cook, 1975;McIntyre et al, 1990), and cobalt hydroxide (782.0 ± 0.1 eV) (Tan et al, 1991). Although Co 2+ possesses a standard reduction potential ( = −0.28 V at 298 K) that is somewhat larger than that of Fe 2+ (= −0.44 V at 298 K), the reduction of Co 2+ by Fe 0 might not take place.…”
Section: Co-loaded Nzvi-kaolsupporting
confidence: 92%
“…31,32 The calculated concentration ratio of oxygen to cobalt (C O /C Co ), CoO 2 ϩ cations are high spin d 8 in octahedral lattice sites and the intense satellite structure has been proposed to result from the charge-transfer band structure found in late 3d transition metal monoxides with partially filled e g character. 15,16,25,[33][34][35] The unpaired nature of the half-filled e g band of the Co 2ϩ cation in CoO results in strong electron correlation and substantial broadening of the cobalt 2p main peaks due to many closely lying 3d final states in photoemission. In contrast, the low-spin, diamagnetic nature of the Co 3ϩ octahedral cation and the weaker crystal field effect of tetrahedral coordination for the There is a second peak at higher binding energy, 531.1 eV at 10%-15% intensity of the main peak.…”
Section: Resultsmentioning
confidence: 99%